(untitled) (Nepalese Journal of Cancer, 2026)
Background: To predict the nature of the adnexal mass, CA-125 is commonly used as a tumor marker. The diagnostic and prognostic value depends on the serum value of CA-125 and the histological variant. This study aims to determine the correlation between serum CA-125 levels and histopathological findings in adnexal masses. Methods: This retrospective study was conducted at a tertiary care cancer hospital. Medical records of patients who underwent surgery for adnexal masses were reviewed. Preoperative serum CA-125 values were categorized into five ranges: <35, 35–135, 136–235, 236–335, and ≥336 U/ml. Histopathological diagnoses were recorded, and the correlation between CA-125 levels and histological types was assessed using Pearson’s correlation coefficient (r). Results: For CA-125 levels <35 U/mL, a very weak positive correlation was noted (r = 0.12), while a moderate negative correlation was found in the 35–135 U/mL group (r = -0.45), indicating malignancy may be present even at lower CA-125 levels. A strong positive correlation (r = 0.60) was observed for CA-125 levels between 136–235 U/mL, mostly associated with serous and mucinous carcinomas. The 236–335 U/mL range showed negligible correlation (r = 0.05), possibly due to histological heterogeneity or small sample size. A very strong positive correlation (r = 0.75) was observed for CA-125 levels ≥336 U/mL, especially with high-grade serous carcinoma. Conclusion: Serum CA-125 levels are variably correlated with histological findings in adnexal masses. Higher CA-125 levels are more predictive of specific malignant subtypes, particularly serous carcinoma, but should be interpreted alongside clinical and radiological findings.